Redetermination of a Claim to Be a Convention Refugee; A Review of the Jurisprudence - Cantin, Roger (Revue générale de droit, 1984)
The refugee determination process under the Immigration Act, 1976 comprises many steps which have been the subject of judicial interpretation. An individual claiming to be a “Convention refugee” in Canada will first be examined under oath with regard to his claim. The Refugee Status Advisory Committee will study the transcript of this examination. After obtaining the advice of the Committee, the Minister of Employment and Immigration will determine whether or not the claimant is a “Convention refugee”. Should this determination be negative, the person concerned will have the choice to apply to the Immigration Appeal Board for a redetermination of his claim. At this stage, the Board will grant an oral hearing to the applicant and render a decision thereafter if it is of the opinion that there are reasonable grounds to believe that he could prove that he is a “Convention refugee”. If no oral hearing is granted, the Board will determine that the applicant is not a “Convention refugee”. The Federal Court and the Supreme Court of Canada have had a considerable input in the interpretation of the provisions relating to this refugee determination process, including the wording of the definition of “Convention refugee”. This paper limits itself to a review of the decisions rendered by these courts.